Spontaneous internal hemorrhage of a giant hepatic hemangioma: A case report. Issue 47 (November 2017) - Hao, Fulong; Yang, Xiaoli; Tian, Yinsheng; Wang, Wenping; Ge, Minggang
Abstract: Rationale: Hepatic hemangioma, a benign liver tumor, can rarely spontaneously rupture and hemorrhage, which is then associated with significant mortality. The diagnosis of internal hemorrhage is challenging and the management is disputed. Patient concerns: We describe the case of a 52-year-old female patient with chief complaints of fever and anemia, with no history of recent trauma. Diagnoses: Ultrasound suggested the possibility of a liver abscess and computed tomography (CT) examination revealed a giant space occupying lesion (SOL) (approximately 16 cm) in the right hepatic lobe, indicating a hepatic tumor or abscess. The patient did not respond to antibiotics and blood transfusion. Liver needle biopsy revealed blood clots suggestive of intratumoral hemorrhage, possibly of a hepatic hemangioma. Interventions: Interventional radiologic approach revealed active bleeding at the phrenic artery that supplied the liver SOL. Thus, embolization was performed and re-angiography showed no active bleeding from the embolized vessel. The patient became afebrile, but fever recurred the next day. Hence, an exploratory open right hemihepatectomy was undertaken and the intraoperative frozen biopsy confirmed hepatic hemangioma with internal hemorrhage, but malignancy could not be excluded for some focal tissues. Postoperative pathology report confirmed the diagnosis of hepatic hemangioma with internal hemorrhage and excluded malignancy. Outcomes: The fever subsided and the patient was discharged in good health. A follow-up CT performed three months, postoperatively, indicated compensatory growth of the left hepatic lobe. Lessons: This case demonstrates that the diagnosis of hepatic hemangioma with internal hemorrhage can be confirmed by needle biopsy and surgical resection is the optimal treatment for such a lesion.